The influence of thermal treatment and type of insoluble poly(meth)acrylates on dissolution behavior of very soluble drug from hypromellose matrix tablets evaluated by multivariate data analysis - Kubova, Katerina; Peček, Daniel; Hasserová, Kristýna; Doležel, Petr; Pavelková, Miroslava; Vyslouzil, Jakub; Muselík, Jan; Vetchy, David (Pharmaceutical development and technology, 2017)
Hypromellose matrices exhibit extended burst effect immediately after contact with aqueous medium, especially when a water-soluble drug is incorporated. The objective of this study was to reduce burst effect and maintain complete dissolution of a very soluble levetiracetam over 12 h period from hypromellose K4M matrices to obtain zero-order kinetics. Desired changes were achieved by applying water dispersions of insoluble Eudragits(®) (NE, NM, RL, RS) as a granulation liquid to the drug/microcrystalline cellulose mixture during high-shear granulation (non-thermal treated set) and consequently by thermally treating granules or final tablets (TT), respectively. Applying Eudragit(®) water dispersions to the drug/microcrystalline cellulose mixture was recognized as an effective method of significantly reducing the burst release (25.4-33.7%) of levetiracetam in comparison with a reference sample without Eudragit(®). Multivariate data analysis showed that the addition of Eudragit(®) reduced burst effect, increased fitting with zero-order kinetics, and supported matrix erosion as the supplementary mechanism to predominant diffusion. Moreover, resulting PCA sub-model revealed the addition of Eudragit(®) RL and thermal treatment of tablets to be the most suitable method of all. For a 12 h dissolution profile, characterized by low burst effect and drug release close to 100% at the 12th hour, sample RL_TT was the most suitable.
Keywords: piracetam; Tablets; tablety; Delayed-Action Preparations; teplota; antikonvulziva; Drug Compounding; multivariační analýza; Piracetam; léky s prodlouženým účinkem; Cellulose; deriváty hypromelózy; kyseliny polymethakrylové; příprava léků; Anticonvulsants; Temperature; Hypromellose Derivatives; Drug Liberation; celulosa; uvolňování léčiv; Solubility; rozpustnost; Polymethacrylic Acids; Multivariate Analysis